SPIRITUALITAS-EROTIS RATU KALINYAMAT [MENAFSIR SIMBOL KECANTIKAN, SEKSUALITAS DAN BIRAHI YANG TERKAIT DENGAN MITOS TOPO WUDHO, WIT JATI BOLONG DAN PELACUR KERATON TERHADAP PILIHAN HIDUP PRAGMATISME-HEDONIS PEREMPUAN JEPARA] - Kholil Lur Rochman (Jurnal Penelitian Agama, 2015)
Abstract: The Queen Kalinyamat genealogically is the daughter of Sultan Trenggono, the third ruler of the kingdom of Demak after Prince Sabrang Lor and Raden Patah. His real name is Retno Kencono ruling as Adipati Jepara area covers Kudus, Pati, Rembang, and Blora. From here can be read, Queen Kalinyamat on one side of the line inherited nobility Sultanate of Demak Bintoro, on the other hand sainthood flowing in his blood because he is the grandson of Raden Patah according to research Widji Saksono, Raden Patah is a member Walisongo fourth period. From this interesting to see why the Queen Kalinyamat who inherited the line of sainthood and nobility in his body lines that should be very familiar with the values and uphold spiritualist aspects of morality. This myth is synonymous with the values-exotic sensuality sex, lust and ambition. Keywords: Queen Kalinyamat, Spintuality, Eroticism galeh nutn dari Sulten Treng